The Monetary-Fiscal Policy Mix: Implications for the Short Run - Brimmer, Andrew F.; Sinai, Allen (American Economic Review, 1986)
In recent years, the policy mix-defined as the contemporaneous joint state of monetary and fiscal policy-has conditioned the patterns of the business cycle, set up numerous imbalances in macroeconomic and microeconomic behavior, and is laying the groundwork for future economic performance. Restrictive monetary and fiscal policies produced back-to-back economic downturns in 1980 and 1981-82. From 1982 to 1985, massive fiscal stimulus against a backdrop of monetary growth targeting by the Federal Reserve comprised a loose fiscal-tight money policy mix. Subsequently, an actual and prospective tightening of the federal budget and suspension of monetary growth targeting suggest a shift in the policy mix to a tight fiscal-easier money combination. In this paper, the policy mix of the 1980's first half-in the context of an open economy with flexible exchange rates-is characterized. Some of the important economic and financial effects are identified. Among these are 1) higher nominal and real interest rates than otherwise would have been the case; 2) a strong domestic currency; 3) lower inflation rates; 4) a large and growing trade deficit; 5) an unbalanced composition of economic activity across sectors and industries; and 6) a depressed industrial sector. Some of the changes in economic performance to be expected as the policy mix is shifted in response to the Gramm-Rudman-Hollings balanced-budget statute also are shown. I. Policy Mix Alternatives, the 1980 to 1985 Episode, and the Analytical Framework